The secret of the totem : religion and society from McLennan to Freud - Jones, Robert Alun (Columbia University Press, 2005)
Robert Alun Jones examines the contentious development of the concept of totemism during the Victorian era. Totemism, whose features include the veneration of an animal or plant, the prohibition of incest, and matrilineal descent, captured the imagination of Sigmund Freud, Emile Durkheim, Sir James Frazer, and other Victorian thinkers. Jones's work combines innovative readings of individual scholars' works with a rich portrait of Victorian intellectual life. Jones considers the divergent ways thinkers drew on totemism to explore religious, cultural, and sexual norms for a civil society. He also examines the reasons behind totemism's eventual demise within intellectual circles.